046 Sporadic Creutzfeldt-Jakob disease in the young: a 10 year review of United Kingdom national surveillance. Issue 9 (12th August 2022) - Tam, Johnny; Centola, John; Kurudzhu, Hatice; Watson, Neil; MacKenzie, Janet; Leitch, Margaret; Green, Alison; Summers, David; Barria, Marcelo
Abstract : Introduction: Sporadic Creutzfeldt-Jakob Disease (sCJD) is the commonest human prion disease, with a median age of onset of 68 years. We aimed to characterise the clinical, investigation, and neuropatho- logical features in young individuals with sCJD using data derived from national CJD surveillance. Methods: We interrogated the NCJDRSU database for individuals diagnosed with definite (post-mortem confirmed) or probable sCJD assessed from 2011-2021. We extracted data on clinical features, MRI, EEG, RT-QuIC, 14-3-3, and PRNP sequencing. Neuropathological findings were also studied where available. This data was compared in young individuals (≤50y) compared to all others. Results: 47 young individuals (4%) were identified (age at onset 25-50) from a total of 1178 cases. 14 (29.8%) were autopsy-confirmed. Psychiatric disturbance at presentation (36.2% vs 22%, p = 0.03) and longer disease duration (by 46 days, 95% CI 15-88, p < 0.01) were commoner in this group. CSF RT-QuIC showed lower sensitivity (81% vs 94%, p=0.01) in younger individuals. There was no difference in the sensi- tivity of MR brain, CSF 14-3-3, or EEG. There were no significant neuropathological differences in autopsy confirmed cases. Conclusions: Younger individuals with sCJD are more likely to present with neuropsychiatric symptoms, longer disease duration, and lower sensitivity of RT-QuIC.